2015
DOI: 10.1016/j.cities.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The creative economy in a context of transition: A review of the mechanisms of micro-resilience

Abstract: This paper assesses the coping mechanisms of creative SMEs in the context of recent economic downturns. It argues that such industries develop various forms of micro-resilience anchored in three main dimensions: production, space and people. By using the case of Digbeth and the Custard Factory as a lens to focus the discussion, it posits the argument that micro-resilience rests upon competitive advantages, including corporate reputation and the capacity of those industries to be flexible, adaptable and entrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 23 publications
3
63
0
3
Order By: Relevance
“…In addition, geographers emphasized "region-specific" or "competitiveness" effects on economic resilience [26]. In this vein of research, literature emphasized the role of place-bound, invisible factors in shaping local economic resilience, such as social values [27], innovation [28], creative small-and-medium sized enterprises (SMEs) [29], entrepreneurship [30,31], as well as the variety of local economic cultures [32]. A recent study identified there exists an inverted U-shaped relationship between local economic embeddedness and resilience [33].…”
Section: Determinants Of Economic Resiliencementioning
confidence: 99%
“…In addition, geographers emphasized "region-specific" or "competitiveness" effects on economic resilience [26]. In this vein of research, literature emphasized the role of place-bound, invisible factors in shaping local economic resilience, such as social values [27], innovation [28], creative small-and-medium sized enterprises (SMEs) [29], entrepreneurship [30,31], as well as the variety of local economic cultures [32]. A recent study identified there exists an inverted U-shaped relationship between local economic embeddedness and resilience [33].…”
Section: Determinants Of Economic Resiliencementioning
confidence: 99%
“…However, the support for the creative economy is mis-focused as it is patently not a normative economic object (the economy); it has a particular compositional (see above) and operational character. The operation of the creative economy is in part generated by its specific organisational structure; a bifurcated form with a few very large firms, and a vast majority not simply small firms, but comprised of micro-enterprises and the self-employed (Andres and Round 2015). Moreover, the enterprises are not of the familiar type; they are best described as serial project-based enterprises (Grabher 2002).…”
Section: The Cultural Fieldmentioning
confidence: 99%
“…The UK's long-running focus on the role of the creative industries in ensuring national, regional and local competitiveness is at this point well-examined (Andres and Round 2015;Cunningham 2002). Schlesinger (2013: 29) notes that 'creativity' is often understood as a synonym for "dynamism, growth, talent formation and national renewal", and that its influence in economic, social and cultural life of the UK shows no sign of abating.…”
Section: From the Creative Industries To The Creative Economymentioning
confidence: 99%